Factor analysis and predictive validity of the Early Risks of Physical Abuse and Neglect Scale (ERPANS): A prospective study in Dutch public youth healthcare. (February 2019) - Schols, Manuela W.A.; Serie, Colinda M.B.; Broers, Nick J.; de Ruiter, Corine
Abstract: Early detection of child abuse risk factors in families of new-born babies is an important task of the public youth health care system in the Netherlands. The Early Risks of Physical Abuse and Neglect Scale (ERPANS) was originally developed in Belgium as an observation scale for public child healthcare nurses. The present longitudinal study is an independent prospective validation of the ERPANS in a Dutch community sample ( N  = 1257) of families with a new-born. Results showed a commonality of underlying subsets of items belonging to the 'Disturbed parent-child relationship' and 'Psychological problems' factors, but the factor 'Communication problems' of the original ERPANS could not be replicated. We found that parental psychological problems were a significant predictor of family problems, including involvement of child protection authorities, at an average follow-up of 22 months. Parents who reported feeling unloved by their own parents were at higher risk of reports of serious concern to child protection authorities at 22 months after birth. These findings support the utility of at least a subset of the ERPANS items as a screening tool for child abuse risk in preventive public youth health care for new-born babies. Our research adds to a growing body of evidence which points to the importance of parental mental health problems and adverse childhood experiences as precursors to child abuse risk.